2017
DOI: 10.1186/s12935-017-0483-x
|View full text |Cite
|
Sign up to set email alerts
|

RAC3 influences the chemoresistance of colon cancer cells through autophagy and apoptosis inhibition

Abstract: BackgroundRAC3 coactivator overexpression has been implicated in tumorigenesis, contributing to inhibition of apoptosis and autophagy. Both mechanisms are involved in resistance to treatment with chemotherapeutic agents. The aim of this study was to investigate its role in chemoresistance of colorectal cancer.MethodsThe sensitivity to 5-fluorouracil and oxaliplatin in colon cancer cells HT-29, HCT 116 and Lovo cell lines, expressing high or low natural levels of RAC3, was investigated using viability assays.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…The development of drug resistance among leukemia cells is the main cause of chemotherapy failure in leukemia patients, which adversely affects prognosis in patients with leukemia 20. Studies have shown that chemoresistance is associated with decreased sensitivity of tumor cells to apoptosis 2122. In this study, we discovered that PIK3CA expression is increased in Nalm-6 cells and that PIK3CA silencing enhances the sensitivity of Nalm-6 cells to chemotherapy drugs (VCR and DNR) by suppressing the phosphorylation of Akt.…”
Section: Discussionmentioning
confidence: 72%
“…The development of drug resistance among leukemia cells is the main cause of chemotherapy failure in leukemia patients, which adversely affects prognosis in patients with leukemia 20. Studies have shown that chemoresistance is associated with decreased sensitivity of tumor cells to apoptosis 2122. In this study, we discovered that PIK3CA expression is increased in Nalm-6 cells and that PIK3CA silencing enhances the sensitivity of Nalm-6 cells to chemotherapy drugs (VCR and DNR) by suppressing the phosphorylation of Akt.…”
Section: Discussionmentioning
confidence: 72%
“…The results indicated the role of RAC3 on endothelial dysfunction by down-regulating autophagy [ 39 ]. Rubio et al demonstrate that the expression level of RAC3 was negatively associated with autophagy, influencing chemoresistance of colorectal cancer [ 40 ]. In a word, RAC3 was verified to have a capacity for down-regulating autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated the role of RAC3 on endothelial dysfunction by down-regulating autophagy [38]. Rubio et al demonstrate that the expression level of RAC3 was negatively associated with autophagy, in uencing chemoresistance of colorectal cancer [39]. In a word, RAC3 was veri ed to have a capacity for down-regulating autophagy.…”
Section: Discussionmentioning
confidence: 99%